OVERCAPITALIZATION HAS LITTLE MEANING. - Martin, T. Leroy (The Accounting Review, 1941)
The article presents information related to overcapitalization as applied to corporations. It is proposed in this paper to discuss critical analysis of currently accepted definitions of overcapitalization, to point out the fallacies upon which they are based and to consider the possibilities of formulating a definition not subject to these criticisms. A U.S. senate bill introduced in 1911 maintained that the registration of any corporation can be revoked by a commission on the ground of overcapitalization that is to say upon the ground that the par value of the total securities including shares of stock and all obligations running for a term of some years or more, of such corporations, issued and outstanding at any time clearly exceeds the true value of the property of the corporation at that time. In determining such true value the said commission shall consider the original cost of such property, its present replacement cost, its present market value, including the goodwill of the corporation's business and the fair value of the services rendered in the organization of such corporation.